2013
DOI: 10.1002/anie.201208021
|View full text |Cite
|
Sign up to set email alerts
|

The Supramolecular Balance for Transition‐Metal Complexes: Assessment of Noncovalent Interactions in Phosphoramidite Palladium Complexes

Abstract: For some decades bidentate ligands have prevailed in the field of transition-metal catalysis. [1] The superiority of bidentate ligands over monodentates was explained by the higher conformational rigidity of the ligands and their stronger coordination to the metal. [1b] However, in the last few years monodentate ligands have experienced a revival, and moreover interest in rational ligand design has grown tremendously: [2] Monodentate ligands have been developed which are able to self-assemble in the coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“… 4 , 22 Additionally, two CH/π interactions between the naphthyl groups of both ligands are apparent in both structures, with H-arene distances within the purview of what has been observed experimentally and computationally for this type of interaction. 23 A structural feature distinguishing between the two diastereomers is the positioning of the dimethyl amino group that is located in 5b under and in close proximity to the cyclobutene ring. This repulsive contact is imposed by the combined hydrogen bond and CH/π interactions.…”
Section: Resultsmentioning
confidence: 99%
“… 4 , 22 Additionally, two CH/π interactions between the naphthyl groups of both ligands are apparent in both structures, with H-arene distances within the purview of what has been observed experimentally and computationally for this type of interaction. 23 A structural feature distinguishing between the two diastereomers is the positioning of the dimethyl amino group that is located in 5b under and in close proximity to the cyclobutene ring. This repulsive contact is imposed by the combined hydrogen bond and CH/π interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, even at 220 K and despite its involvement in quite strong intra-and interA C H T U N G T R E N N U N G liA C H T U N G T R E N N U N G gand interactions, the rotation of the amine group about the P À N bond in cis-[Pd1 2 Cl 2 ] is still fast enough to cause a transfer of NOE contacts during a mixing time of 750 ms. [36] At first glance, such rotational processes seem to hamper the discussion of specific intermolecular interactions, but it is well known for intermolecular interactions that enthalpic and entropic contributions do compensate each other to a large extent. [26] Thus, the presence of rotational processes does not affect the quantification and discussion of ligand interactions, as long as exclusively DG values are discussed, which are generally very robust with respect to temperature-dependent changes in DS and DH, for example. On the other hand, several rotational degrees of freedom within the ligands can act as a universal joint and allow for an optimal orientation of interaction areas.…”
Section: Structural Properties Of Trans and Cis Complexes And Interamentioning
confidence: 99%
“…Recently, we showed that the combination of enantiopure ligand 1 with the enantiomeric ligands 2 or 2* allows a direct energetic connection of the two complex equilibria. [26] Since the homo-complex cis-[Pd1 2 Cl 2 ] is identical within both complex equilibria and the respective second homocomplexes cis-[Pd2 2 Cl 2 ] and cis-[Pd2* 2 Cl 2 ] are enantiomeric, the free energies of the homo-complexes are identical for both complex equilibria. Therefore, the excess formation of cis-[Pd(1)(2*)Cl 2 ] directly provides the energetic stabilization of cis-[Pd(1)(2*)Cl 2 ] compared to cis-[Pd(1)(2)Cl 2 ].…”
Section: Since Only One Amine Side Chain Interacts With the Biaryl Bamentioning
confidence: 99%
See 2 more Smart Citations